Ultrasensitive detection and phenotyping of CD4+ T cells with optimized HLA class II tetramer staining. - Scriba, T; Purbhoo, M; Day, C; Robinson, N; Fidler, S; Fox, J; Weber, J; Klenerman, P; Sewell, A; Phillips, R (2005)
HLA class I tetramers have revolutionized the study of Ag-specific CD8+ T cell responses. Technical problems and the rarity of Ag-specific CD4+ Th cells have not allowed the potential of HLA class II tetramers to be fully realized. Here, we optimize HLA class II tetramer staining methods through the use of a comprehensive panel of HIV-, influenza-, CMV-, and tetanus toxoid-specific tetramers. We find rapid and efficient staining of DR1- and DR4-restricted CD4+ cell lines and clones and show that TCR internalization is not a requirement for immunological staining. We combine tetramer staining with magnetic bead enrichment to detect rare Ag-specific CD4+ T cells with frequencies as low as 1 in 250,000 (0.0004% of CD4+ cells) in human PBLs analyzed directly ex vivo. This ultrasensitive detection allowed phenotypic analysis of rare CD4+ T lymphocytes that had experienced diverse exposure to Ag during the course of viral infections. These cells would not be detectable with normal flow-cytometric techniques.